Faktor-faktor yang mempengaruhi keberkesanan amalan pengurusan kualiti menyeluruh (TQM) terhadap pekerja sokongan di sektor telekomunikasi - Noresmawati, Binti Ismail. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The purpose of this study was to highlight the factors that influence the effectiveness of TQM implementation among supportive workers in telecommunication sector. The factors that contribute to the effectiveness consist of continuous improvement, empowerment, teamwork and customer focus. The study was conducted among supportive staffs at Menara Celcom Northern Region in Burma Road, Penang. The primary data was analyzed using Statistical Package for the Social Sciences (SPSS-Windows Version 11.0). The result shows that there are three factors which in continuous improvement, empowerment and teamwork that have a strong relationship with the effectiveness of TQM implementation among supportive workers in telecommunication sector while customer focus did not have a relationship ti ith the effectiveness. The relationships were analyzed using Correlation Pearson and score measure the level of effectiveness. Overall, customer focus is very important to the effectiveness of TQM implementation among supportive workers in telecommunication sector. It is need to be a focus to make sure the effectiveness of TQM implementation.